Hot deformation characteristic and processing map of superaustenitic stainless steel S32654 - Pu, Enxiang; Zheng, Wenjie; Xiang, Jinzhong; Song, Zhigang; Li, Ji (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2014)
The hot deformation behavior of superaustenitic stainless steel S32654 was studied in the temperature range of 950-1200 degree C and strain rate range of 0.001-10s-1 employing hot compression tests. The results show that peak stress increases with decreasing of temperature and increasing of strain rate. The apparent activation energy of this alloy is about 469kJ/mol. The processing maps for hot working were developed on the basis of flow stress data and the dynamic materials model. It is found that the features of the maps obtained in the strain range of 0.2-1.0 are fundamentally similar, indicating that the strain does not have a significant influence on processing map. The maps exhibited two domains. The first domain occurs in the strain rate range of 0.01-0.4s-1 and temperature range of 1030-1150 degree C with a peak efficiency of about 49%, which is considered as the optimum window for hot working. The microstructure observations of the specimens deformed in this domain showed the full dynamic recrystallization (DRX) structure with finer and more homogeneous grain sizes. The second domain occurs at the temperatures higher than 1160 degree C and strain rates lower than 0.1s-1 with a peak efficiency of about 41%, the microstructure observations in this domain also indicated the typical DRX structure accompanied with grain growth. A instability domain occurs at temperatures below 1175 degree C and strain rate above 0.1s-1.